2017
DOI: 10.21037/jgo.2017.01.26
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant transarterial radiation lobectomy for colorectal hepatic metastases: a small cohort analysis on safety, efficacy, and radiopathologic correlation

Abstract: Colorectal cancer patients have a high incidence of liver metastasis (ml-CRC). Surgical resection is the gold standard for treatment of hepatic metastasis but only a small percent of patients are traditional candidates based on disease extent and adequate size of the future liver remnant (FLR). Interventions such as portal vein embolization (PVE) and associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) are performed to increase FLR for operative conversion. Limitations to PVE inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…While our study was not aimed to determine prognostic predictors for hepatectomy success in post-TARE patients, an interesting future area of investigation that has already been begun by Shah et al 24 The intent of TARE was not specified in many of our cases, so another future area of investigation would be to track the growth of FLR before and after TARE for those patients who receive radiation doses directly intended for contralateral hypertrophy. Melstrom et al 10 is the only study we found that has attempted to determine prognostic factors of major complications post-hepatectomy, but the activity of Y-90 was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…While our study was not aimed to determine prognostic predictors for hepatectomy success in post-TARE patients, an interesting future area of investigation that has already been begun by Shah et al 24 The intent of TARE was not specified in many of our cases, so another future area of investigation would be to track the growth of FLR before and after TARE for those patients who receive radiation doses directly intended for contralateral hypertrophy. Melstrom et al 10 is the only study we found that has attempted to determine prognostic factors of major complications post-hepatectomy, but the activity of Y-90 was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In a small cohort study of four patients with inadequate FLR who underwent systemic chemotherapy and RL prior to resection, FLR hypertrophy ranged from 25 to 119% at a mean follow-up of 3 months; hepatectomy specimens demonstrated complete pathological response in 50% of patients. 56 In a separate population of patients with hepatocellular carcinoma, two studies reported only transient hepatobiliary toxicities, with the majority of resected tumors having >50% pathological necrosis among patients who underwent RL followed by resection. 55,57 A systematic review of several series using Y-90 reported FLR hypertrophy of 26 to 47% within 9 months.…”
Section: Strategies To Increase the Future Liver Remnantmentioning
confidence: 98%
“…4), including neoadjuvant lobar treatments, in challenging locations while having minimal toxicity on adjacent structures. 90,91 Radioembolization relies on suitable arterial tumor conduit and adequate margin within the targeted angiosome. Systemic therapies which alter tumor vascularity (e.g., bevacizumab or sorafenib) may affect treatment outcomes.…”
Section: Radiationmentioning
confidence: 99%